PENERAPAN KONSEP MASLAHAH DALAM KONSUMSI UNTUK MENCAPAI MAXIMUM UTILITY - Suryani, Zulfa; Taufiq, Muhammad (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to find out about the application of the maslahah concept in public consumption in the Lasi district to achieving maximum utility. This research uses a descriptive qualitative approach using interview data collection techniques. The informants in this study were the people in the Lasi district with a total of 30 informants. The selection of informants was carried out by accidental sampling technique. From the results of the research conducted, it was found that maslahah can only be obtained when consumption is carried out on goods in accordance with Islamic law, not exaggerating in fulfilling consumption goods and in terms of achieving maximum utility, society prioritizes the principle of spiritualism in achieving happiness both in this world and in the hereafter by means of zakat, infaq and alms.